Challenges in Screening and Diagnosing Frailty Syndrome: Which Tool to be used? - Purwita W Laksmi (Interna Publishing, 2016)
Frailty syndrome has become one of the geriatric syndromes with an increasing risk of debilitating clinical outcome. Accordingly, the current treatment guidelines have been focusing in viewing frailty syndrome as an important aspect to be considered. The International Diabetes Federation (IDF) classifies the guideline for managing the elderly with type 2 diabetes mellitus based on their functional status, whether it is functionally independent or dependent. Functionally dependent group is further classified as subgroup of frail and/or demented people. Special consideration on older people has also been discussed as a topic on the treatment algorithm for hypertension and dyslipidemia.